2014
DOI: 10.1111/jpc.12727
|View full text |Cite
|
Sign up to set email alerts
|

What has changed from 2001 to 2012 for sexual minority youth in New Zealand?

Abstract: Aim: To provide an overview of the health and wellbeing of sexual minority high school students in New Zealand, investigate differences between sexual minority youth (SMY) and exclusively opposite-sex attracted youth (EOSAY) and examine changes across survey waves. Conclusions:Health services, schools, communities and families must be more responsive to the needs of SMY, to ensure that disparities are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
4
30
0
1
Order By: Relevance
“…Comparisons with other research are hampered by differences in sampling, the types of drugs examined and the recall period between studies. The high proportion of participants reporting drug use is consistent with New Zealand research indicating elevated rates of substance use among GBM and is greater than the 23% of the New Zealand male population aged 16–64 years who reported drug use in the previous year in a 2007/2008 national survey . Internationally, our participants appeared to show similar rates of cannabis and poppers use to GBM surveyed in gay community settings in Australia at the same time , higher rates of cannabis compared with GBM in the UK and lower rates of other illicit and club drugs .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Comparisons with other research are hampered by differences in sampling, the types of drugs examined and the recall period between studies. The high proportion of participants reporting drug use is consistent with New Zealand research indicating elevated rates of substance use among GBM and is greater than the 23% of the New Zealand male population aged 16–64 years who reported drug use in the previous year in a 2007/2008 national survey . Internationally, our participants appeared to show similar rates of cannabis and poppers use to GBM surveyed in gay community settings in Australia at the same time , higher rates of cannabis compared with GBM in the UK and lower rates of other illicit and club drugs .…”
Section: Discussionsupporting
confidence: 80%
“…The high proportion of participants reporting drug use is consistent with New Zealand research indicating elevated rates of substance use among GBM and is greater than the 23% of the New Zealand male population aged 16–64 years who reported drug use in the previous year in a 2007/2008 national survey . Internationally, our participants appeared to show similar rates of cannabis and poppers use to GBM surveyed in gay community settings in Australia at the same time , higher rates of cannabis compared with GBM in the UK and lower rates of other illicit and club drugs . Further analysis of Australian data has indicated that 2006 represented a peak in drug use, which then declined and similar trends may have occurred in New Zealand since our data were collected.…”
Section: Discussionsupporting
confidence: 80%
“…In a smaller study of health and adjustment in 245 GLBT young people aged 21 to 25, family acceptance (based on two to four hour in depth interviews) predicted greater self‐esteem, social support and general health but also lower levels of ‘suicidal thoughts or behaviour’ (Ryan et al ., ). It may be that gender orientation and/or identity per se account for only a small proportion of variability in suicidal ideation and attempts, with risk largely mediated through the presence (or not) of protective factors such as perceptions of family support and ‘acceptance’ and this may also vary by gender, with males being particularly vulnerable (Lucassen et al ., ).…”
Section: Child Characteristicsmentioning
confidence: 97%
“…11 While there appears to be improvements in reproductive health, there are disparities in rates of STIs and in rates of access to sexual health services among some populations. [12][13][14] Tracking trends in sexual health behaviours among adolescents is essential for any evidence-based public health intervention to monitor progress, ascertain weaknesses in the delivery of sexual and reproductive healthcare, and identify populations vulnerable to unplanned pregnancies and STIs. In this study, we present data from the Youth2000 survey series; these are nationally representative health and wellbeing surveys of secondary school students in NZ.…”
mentioning
confidence: 99%